Headache triggered by coronavirus disease 2019 vaccination increases in line with history of allergic disorders and comorbidities like depression and fibromyalgia: An analysis of the US vaccine adverse event reporting system - Yilmaz, Gülcan Göçmez; Murzakhanov, Nazlican; Yildirim, Didem Derici; Baykan, Betül; Garcia-Azorin, David; Frontera, Jennifer A.; Winkler, Andrea Sylvia; Özge, Aynur (Wolters Kluwer - Medknow, 2023)
Background: Headache is the most common neurological side effect of coronavirus disease 2019 (COVID 19) vaccination. However, the underlying reason for COVID 19 postvaccine headache has not been fully understood. In this study, we addressed the potential association of vaccine related headaches with a history of allergy, atopic diseases, as well as other comorbid conditions to gain insight about the pathophysiology of this headache. Materials and Methods: This study analyzed the data from the Vaccine Adverse Event Reporting System database and reorganized dataset accordingly. The study included individuals aged 16–85 years who received the first or second dose of COVID 19 vaccines approved by the Food and Drug Administration. Allergy and atopic disease histories (reported food or drug allergy, allergic rhinitis, asthma, and other autoimmune diseases) and other accompanying diseases such as depression, anxiety, sleep disorders, fibromyalgia, and obesity of these subjects were examined from the revised data, and their relationship with COVID 19 vaccine related headaches was investigated. Results: We found a statistically significant positive association in patients with a history of headache after COVID 19 vaccination and reported a history of allergy (P < 0.001). In the allergy subgroup (n = 14547 [37.1%]), the frequency of headaches following COVID 19 vaccine was found to be higher in those with drug, food, and/or multiple allergies (P < 0.05). A statistically significant relationship was disclosed between asthma, autoimmune diseases, and headache, but no association was found with allergic rhinitis (P < 0.001, P = 0.160). Furthermore, the rate of headaches after vaccination was found to be higher in people with fibromyalgia and depression (P < 0.001, both). Conclusion: Significant associations between headaches triggered by the COVID 19 vaccine and histories of allergy, fibromyalgia, and depression may suggest a shared predisposing mechanism for pathophysiology. Knowledge about allergy history and related comorbid conditions can be helpful in predicting COVID 19 vaccine headache. Future prospective data may provide further enlightenment on management.